The Julio-Claudian succession : reality and perception of the "Augustan model" - Gibson, A. G. G. (Mnemosyne, Supplements, 2012)
This collection of essays considers the challenging questions around the formation, establishment and continuation of the Julio-Claudian principate from the coming to power of Augustus. Augustus laid down the ground rules for a princeps , and the essays explore the subsequent transition of power, and how the succession and subsequent rule manifested itself, even though there was no formal mechanism for such a transfer. These essays fully utilize the extant literary, epigraphic, numismatic and visual record to evaluate Augustus' "political legacy". The representation, and retention, of power was a critical issue for the princeps and his subjects, and the contributors provide fresh political and literary analysis of aspects of the principates of Augustus, Tiberius, Claudius and Nero.